الحصيات المرارية وسرطان المرارة - قنجراوي, أكثم (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 33 حالة سرطان مرارة من أصل 1825 مريضٍ خضعوا لاستئصال مرارة بين عامي 1992 و2007 في مشفى الأسد الجامعي باللاذقية. نسبة الإناث إلى الذكور 1:2.3 نسبة ترافق سرطان المرارة مع الحصيات هي 93.9 %. تزداد نسبة حدوث السرطان مع الحصيات < 2 سم والحصيات العديدة و زيادة فترة بقاء الحصيات في المرارة. 75.75% من المرضى كانوا مدخنين مع حمية عالية الحريرات ويشربون القهوة. العمر الوسطي للإصابة بالسرطان هو 58 سنة. وجّه الإيكو للسرطان عند 19 مريضاً فقط إلى بنسبة 57.57% .تمت المعالجة الجراحية الجذرية عند 19 مريضاً بنسبة 57.57% في I و II حسب تصنيف Nevin- Moran . كان معدل الوفيات لمدة 6 أشهر 60.6%. تشابه أعراض سرطان المرارة أعراض القولنج المراري ، ويكون تشخيصه في أكثر الحالات بالصدفة أثناء الجراحة وله علاقة وثيقة بالحصيات المرارية وذو إنذار سيء جداً. This study includes 33 cases of gallbladder carcinoma (GBC) out of 1825 patients who have undergone cholecystectomy between 1992 and 2007 at Al-Assad University Hospital in Lattakia. Females/males=2.3/1. The percentage of associating Gallstones with GBC is 93.9%. The incidence of carcinoma increases with stones > 2 cm multistones, and long standing gallstones. 75.75% of patients are smokers and on a high calorie diet and drink coffee. The average age of patients is 58 years. Carcinoma is detected by echography in 19 patients (57.57%).Radical surgery is operated on 19 patients (57.57%). Fatality rate for 6 months has been 60.6%. Symptoms of GBC, like those of biliary colic, are diagnosed in surgery by chance in most cases and are closely related to Gallstones. GBC carries too bad a prognosis.